Раціоналізація спільної роботи залізничних станцій у вузлі - Крячко, К. В.; Шрамко, А. М.; Коврига, В. В.; Kryachko, К.; Shramko, А.; Kovriga, V. (ЦНТУ, 2023)
В даній роботі рекомендуються варіанти оптимального перерозподілу сортувальної і маневрової роботи між сортувальними та вантажними станціями при формуванні передаточних поїздів з можливістю урахування детального підбору окремих груп вагонів на окремі вантажні фронти. Це дає змогу раціонального використання сортувального пристрою та маневрових локомотивів як на технічній, так і на вантажних станціях, а також зменшення тривалості знаходження місцевих вагонів під час здійснення основних технологічних операцій у залізничному вузлі. In this work the variants of rational technology for the redistribution of the sorting and shunting work between sorting and freight stations in the formation of the gear trains, taking into account possible detailed the selection of individual groups of cars for specific cargo fronts .This gives the possibility of optimal use of screening devices and shunting locomotives as sorting and freight stations, as well as the reduction of the length of time of local cars during the execution of the basic technological operations in the railway node. The studies of the structure of volumes with the processing of coming to the sorting stations, it was found that of the total local traffic volume ranges from 7% to 12% and the accumulation time of trains gear trains – up to 8 hours or more. Given that the time for the completion of the formation of these compounds through an slide in the rail yard for much less than freight (depending on the number of groups of wagons ) and that the cost of recycling of one car on the yard and station at 5 – 6 times less than the cargo, was asked to undertake the completion of the formation to the exactions of railway freight fronts in the rail yard, especially at this time when the reduction in the total amount of work sorting slides have sufficient reserve processing capacity. The dependences for determining the number of groups of wagons with defined assignment freight station in trains transfer trains, as well as finding the average number of uncoupling , which determines the amount of shunting work on the exhaust paths.
Rationalization of Joint Work of Railways Stations in the Node
Keywords: передаточні поїзди; залізничний вузол; залізничні станції; вантажні перевезення; маневрові локомотиви; transfer trains; railway junction; railway stations; freight transport; shunting locomotives